Pendidikan sebagai Reproduksi Nilai Menurut Ibnu Khaldun dan Implementasinya di SMP Islam Amanah Ummah - Hasan, Ismail; Fauzi, Sriyono (Lembaga Yasin AlSys, 2024)
Many philosophers have contributed their thoughts to the field of education, including Ibn Khaldun. He was a bold individual who introduced innovative ideas. Specifically in the realms of knowledge and education, he successfully mapped and positioned Islamic and general knowledge effectively, making it easy for anyone to study and conduct further research. This study aims to analyze Ibn Khaldun's thoughts on education as the reproduction of values and its implementation in Amanah Ummah Junior High School, Sukoharjo. The research employs a qualitative method (Field Research). The results obtained by the author include the following: concerning the aspect of Islamic educational goals, Ibn Khaldun's perspectives are; 1) shaping the Complete Individual (Insan Kamil), 2) the importance of teachers having models and approaches in teaching, 3) using techniques appropriate to the subject matter, and 4) implementing knowledge into positive values.